HASIL JAGUNG PADA TUMPANGSARI DENGAN KARABENGUK (Mucuna pruriens L.(dc.)) MUSIM HUJAN DAN KEMARAU - Supriyono Supriyono (Universitas Sebelas Maret, 2008)
The aim of this research was request: What was the effect of planting season on marginal region miaze growth anad yield? What was the effect of velvet bean with different times planted and cultivars on maize growth and yield? What was the effect on interaction of seasons and velvet bean on maize growth and yield?This research was conducted on litosol soil in Tancep, Ngawen, Gunungkidul on 170 m up sea level and 9-10o elevation. The depth of soil tillage was 5-17 cm. Design utilization was Randomized Completed Block Design (RCBD) with factorial 2 factors. The treatment was 1) planting seasons: rainy and dry season 2) cultivars and velvet bean time planting: 1) control, monoculture corn, 2) corn and the same time Rase cultivar of velvet bean, 3) corn and the same time Putih Gunungkidul cultivar of velvet bean 4) corn and 2 weeks Rase cultivar of velvet bean planted after corn, 5) corn and 2 weeks Putih Gunungkidul cultivar of velvet bean planted after corn, 6) corn and 4 weeks Rase cultivar of velvet bean planted after corn, 7) corn and 4 weeks Putih Gunungkidul cultivar of velvet bean planted after corn. There is replicated 3 times.The 1st corn and 4 weeks velvet bean planted after corn produced higher seed per plant and per plot than monoculture corn. That data was also supported by 100 seed weight. The 2nd, corn with velvet bean on rainy season did not straw for animal feed harvest caused by the big velvet bean growth and long time harvest after corn. The 3rd, two fact recommended that corn increased yield on marginal region and dry season given by 4 weeks velvet bean planting after corn.